Quando os bombeiros não chegam: algumas contribuições da psicologia do trabalho para o entendimento dos acidentes com veículos operacionais de bombeiros na região metropolitanade Belo Horizonte - Andreia Geraldo Batista (2009)
This study aimed to understand an increase in accidents envolving operational vehicles from the Fire Department Units of the Metropolitan Region of Belo Horizonte. The demand was presented to the Psychology department by the Operational Commander of the Military Fire Department of Minas Gerais who observed a significant increase in accidentsrate in early 2007. The work began gathering all available records on accidents which confirmed the perceived increase (131.81%). After that, The stages of Work Analysis (WA) and Psicosociological Work Analysis (PWA) were proceeded, in order to comprehend the activity developed by those workers, as well as its subjective impacts. At last, some case studies were held as part of PWA, which helped to understand the individual consequences of the problems which were identified in the early stage of EWA. In the first case, we analyzed an accident envolving a rescue vehicle to show that its cause, which seemed to be simple, in fact was a result of a complex combination of factors. In the second case, we brought two examples of near-accidents, showing that these events pre-accidents are also important when thinking about safety of drivers at work, offering important contributions to understand the development of the accidents. The study found that factors such as long hours of shift-work, poor material conditions that compromising the rest time, as well as the strictiveness of rules and organization of their activities have affected the adjustment strategies these workers usually use to face the challenges imposed by their activity.